Intrabiliary Hepatic Metastasis of Colorectal Carcinoma Mimicking Primary Cholangiocarcinoma: A Case Report and Review of the Literature. (26th June 2016) - Dong, Yimin; Patel, Hitendra; Patel, Charmi
Abstract : Intrabiliary metastasis from colorectal carcinoma (CRC) growing within or invading bile ducts is not a very common pattern. However, accurate diagnosis of metastatic lesions is very important for selection of adjuvant therapy and prognosis. We report a case of 71-year-old male who developed painless jaundice due to hepatobiliary obstruction. MRI demonstrated 1.4 cm intraductal mass at hepatic hilum with severe intrahepatic ductal dilation, consistent with cholangiocarcinoma. ERCP (endoscopic retrograde cholangiopancreatography) showed intraductal segmental biliary stricture. Biopsy from the lesion showed adenocarcinoma favoring primary cholangiocarcinoma due to the papillary morphology and location of the mass. His past history was significant for rectosigmoid carcinoma (pT1N0) ten years ago and liver resection for metastatic CRC four years ago. He subsequently underwent central hepatectomy with resection of common bile duct. Grossly, there was a 1.2 cm intraductal mass at the bifurcation of bile ducts with multiple nodules in liver parenchyma. Microscopic examination revealed intraductal carcinoma with papillary architecture colonizing bile duct epithelium with resultant dilation and tortuosity. Occasional liver parenchymal nodules show classical metastatic pattern resembling CRC. Because of two distinct morphologic patterns and patient's past history, immunostains were performed. CK7 stained uninvolved bile duct epithelium with no staining in intrabiliary metastatic growth. CK20 and CDX2 were positive, thus confirming intrabiliary growth as metastatic growth from CRC. In summary, findings from our case indicate that intrabiliary growth of metastatic CRC can easily be overlooked with major duct involvement. Pathologic evaluation with use of immunohistochemical stains is very important to achieve correct diagnosis.